2001
DOI: 10.1017/s0030605300031537
|View full text |Cite
|
Sign up to set email alerts
|

Community attitudes and behaviour towards conservation: an assessment of a community conservation programme around Lake Mburo National Park, Uganda

Abstract: This paper analyses the impact of a community conservation programme (CCP) implemented over a 7-year period around a national park in Uganda. Programme activities included dialogue, con¯ict reduction, education, community resource access and support for community development. Surveys of attitudes show that communities bene®ted from the programme were signi®cantly more positive towards the park and wildlife than communities that did not. The community conservation programme built an understanding of conservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 19 publications
9
83
3
4
Order By: Relevance
“…A substantial proportion of the annual funding for conservation activities in ACA was, until the recent Maoist action, financed through tourist revenues (Gurung 2005). Similar infrastructural development benefits have been reported from other community-based projects elsewhere (Metcalfe 1994;Pearl 1994;Wainwright and Wehrmeyer 1998;Infield and Namara 2001;Kangwana and Mako 2001). An overwhelming majority of respondents in the conservation area expressed satisfaction with social service developments.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A substantial proportion of the annual funding for conservation activities in ACA was, until the recent Maoist action, financed through tourist revenues (Gurung 2005). Similar infrastructural development benefits have been reported from other community-based projects elsewhere (Metcalfe 1994;Pearl 1994;Wainwright and Wehrmeyer 1998;Infield and Namara 2001;Kangwana and Mako 2001). An overwhelming majority of respondents in the conservation area expressed satisfaction with social service developments.…”
Section: Discussionsupporting
confidence: 72%
“…One possible solution is to give more authority and responsibility to local communities to manage wildlife for their crop protection. However, this issue is controversial (Infield and Namara 2001), especially where some of the animals concerned are threatened with extinction. It has been argued that the future success of conservation in Nepal depends on the ability to provide local villagers with sufficient and varied resources to secure their livelihoods (Studsrod and Wegge 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several respondents who get cash income highly had better attitudes on protection forest. This is in line with other studies from Badola et al (2012) and Infield and Namara (2001) which showed that local communities will hold positive attitudes towards forest management and conservation if they received many benefits from forest.…”
Section: Resultssupporting
confidence: 79%
“…That is why understanding local community knowledge and attitudes on protection forest conservation and the sustainable management of natural resources is crucial (Triguero-Mas et al 2010). The studies of local community attitudes have also contributed to a better understanding of local people needs and aspirations for conservation (Infield & Namara 2001). Therefore, this study aims to develop community empowerment strategies using bottom-up approaches that consider local community knowledge, attitudes, needs, wishes, and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Information on perceptions and attitudes of local communities living in and around protected areas is important to identify management programmes and strategies that best suit the protection of biodiversity alongside the development of local community livelihoods (Heinen, 1993;Infield and Namara, 2001;Allendorf, 2007;Kideghesho et al, 2007). Moreover, understanding of the attitudes of local communities, particularly where their rural livelihoods are dependent on agriculture is vital for resolving wildlife-human conflicts, which otherwise can threaten the success of any conservation activity (De Boer and Baquete 1998;Webber et al, 2007).…”
Section: Introductionmentioning
confidence: 99%